Effect of ceramic dental waste in thermo-physical properties of materials composed with polyester resins - Martínez-Maldonado, Lorena; Peña-Rodríguez, Gabriel (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2014)
Thermophysical properties at room temperature of a composite material based on polyester resins and powders obtained from dental ceramic residues for mixtures with percentage by weight of 50-50, 60-40, 70- 30, 80-20 and 90-10 are recorded, where the minority phase are dental ceramic powders with particle size through sieve No. 200 (75 um), and the majority of pre-accelerated polyester resin brand P-2000, and as catalyst (Meck-Peroxide). The manufacturing process of the specimens was by casting them into cylindrical molds of diameter 3 cm and 6 cm long. The properties of conductivity (k) and thermal diffusivity (α) and the specific heat per unit volume (ρc), were found using the KD2 Pro® system which operates on the physical principle of linear transient heat flow. Thermal effusivity (ε) was determined using data from k and α, and the expression ε = k/√ α. The results show that as the percentage of the ceramic powder is increased, the density of the samples increases, and thus the thermal conductivity (k), which is directly proportional to both heat diffusion rate (α) and the amount of heat that the material can store or release (ρc). These results suggest a new material for technological applications, as well as they help to mitigate the environmental impact due to the recycling process of dental ceramic waste.